KOMUNIKASI POLITIK PARA ELIT DI ERA VIRTUAL CULTURE - Lilik Sumarni (Universitas Muhammadiyah Jakarta, 2018)
A virtual world had been created to join the world of reality. Activities of political elites, especially in a political setting, with the efficacy of the strategy by clicking and engineering the public opinion of discourses; war discourse by harnessing the power of media. Social media in a time vortex became a very significant machine to determine our lifestyles, political attitudes in addition to bring online a very lucrative business online, including politics. Mingling of political and economic interests became so dominant in the realm of the media industry. The presence of social cyber space provided a new perspective in understanding the development of political discourse. In this virtual world era, the current information relating to politics is easy to obtain and there had been a fatality information that ended up being a mockery, entertainment and humor that no longer had a value, function and meaning, they were mingled and distorted by the capitalist interests who only promote business oriented alone regardless of content. The presence of social media became an implement of shaping the new culture included culture and attitudes of political elites, mirror-imaging and political marketing that had created divisions and made the boxes of support political for the political actors with political advertising strategy in the form of imaging. Accommodations of mass media for the image of politics were understood in the perspective of the economy, especially in the law of supply and demand that became the logical characteristic and market regulation. When politic become a commodity, and ultimately the reality of elections can be capitalized, the media and the public image of political cyber regarded as legitimate and so natural, and everyone is free to create strategies to meet their interests.Keywords: Political Communication, Elites, Virtual Culture